1980
DOI: 10.1111/j.1365-2605.1980.tb00130.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Clomiphene Citrate on Testicular Steroid Metabolism in Man

Abstract: Administration of clomiphene citrate to males with normal peripheral testosterone levels increased the serum levels of FSH, LH, testosterone and low polar oestrogens and also the urinary excretion of LH, low polar oestrogens, dehydroepiandrosterone, androsterone and aetiocholanolone. No significant change was noted for the urinary excretion of 17-oxogenic steroids. Addition of clomiphene citrate (10(-4) to 2 X 10(-3) M) to incubations of [7-3H, 21-14C] progesterone with human testicular biopsy specimens in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1984
1984
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 38 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…In vitro steroidogenesis has not been reported to be significantly impaired by such storage [4,12,231.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro steroidogenesis has not been reported to be significantly impaired by such storage [4,12,231.…”
Section: Discussionmentioning
confidence: 99%
“…Previous information concerning the rate of human testicular steroid conversion in vitro was obtained utilizing incubation with radiolabeled precursors [2,4,12,15,18,21,221. In the present study the conversion of pregnenolone in vitro by testicular tissue from human males of different ages was analyzed using a standard technique.…”
Section: Discussionmentioning
confidence: 99%
“…Clomiphene citrate is a synthetic nonsteroidal com pound with a weak estrogen activity which behaves as a potent antiestrogen agent in man, since its main function is to compete for estrogen receptors in the hypothalamus and pituitary gland [24,25]. This interaction neutralizes the negative feedback control of estrogens resulting in a rise of LH and FSH secretion [26] and subsequently inducing an increase in testosterone and sperm production by the testis [24,27], This characteristic allows us to use this drug to investigate the integrity of the gonodal axis in men [28].…”
Section: Discussionmentioning
confidence: 99%
“…This interaction neutralizes the negative feedback control of estrogens resulting in a rise of LH and FSH secretion [26] and subsequently inducing an increase in testosterone and sperm production by the testis [24,27], This characteristic allows us to use this drug to investigate the integrity of the gonodal axis in men [28]. On the other hand, it has been widely used to treat hypogonad ism and infertility [29,30], It has been reported that clomi phene citrate produces a normal or subnormal response of LH and FSH in uremic males which can restore testos terone levels to normal values [30], However, its effects on prolactin secrection in uremic males have not been clearly defined yet.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11] Its relationship with plasmatic and urinary level variations of 17-hydroxyprogesterone, testosterone and luteinizing hormone has been described too. [12][13][14] The aim of this work was to carry out an excretion study of clomiphene in human urine with the purpose to detect and to identify some of not previously reported metabolites after a multiple oral administration dose of clomiphene citrate to healthy volunteer using gas chromatography-mass spectrometry. Also, changes on endogenous steroids profile that can be used to diagnose clomiphene consumption were evaluated.…”
Section: Introductionmentioning
confidence: 99%